Fairy tail. 13 - Mashima, Hiro, 1977- (Del Rey/Ballantine Books, 2011)
"Master Makarov's grandson, the too-powerful wizard Laxus has seen the new Fairy Tail guild hall and doesn't like what he sees! So he gathers some of the strongest wizards in the guild, and starts a Fairy Tail civil war!"-- P. [4] of cover.